2000
DOI: 10.1007/pl00008872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liana cutting on water potential and growth of adult Senna multijuga (Caesalpinioideae) trees in a Bolivian tropical forest

Abstract: Lianas, or woody climbing plants, are a major constituent of seasonally dry tropical forests, and are thought to impact negatively their host trees. In this study we evaluated whether liana presence was associated with reduced leaf water potentials and growth in adult Senna multijuga trees during the dry season in a lowland Bolivian forest. We used leaf water potentials in trees as a first approach to assess trees' water status, under the assumption that leaf water potentials become more negative when water lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
124
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(144 citation statements)
references
References 39 publications
12
124
1
7
Order By: Relevance
“…The finding that liana strongly affected the distribution pattern and decomposition degree of surface litter supports the conclusion that the spatial heterogeneity of forest floor litter is regulated by the distribution of trees as well as the understory plants [27,28]. The differences in litter …”
Section: Effect Of Liana On Litter Distributionsupporting
confidence: 76%
See 1 more Smart Citation
“…The finding that liana strongly affected the distribution pattern and decomposition degree of surface litter supports the conclusion that the spatial heterogeneity of forest floor litter is regulated by the distribution of trees as well as the understory plants [27,28]. The differences in litter …”
Section: Effect Of Liana On Litter Distributionsupporting
confidence: 76%
“…The finding that liana strongly affected the distribution pattern and decomposition degree of surface litter supports the conclusion that the spatial heterogeneity of forest floor litter is regulated by the distribution of trees as well as the understory plants [27,28]. The differences in litter components between stands with different densities of liana were attributed to the physical and biological characteristics of the liana plant [14,29].…”
Section: Effect Of Liana On Litter Distributionsupporting
confidence: 75%
“…Reduced below-ground liana competition may be particularly important during seasonal drought when declining soil moisture availability may limit canopy tree uptake, because lianas continue to grow and take up below-ground resources during this period (Andrade et al 2005, Schnitzer 2005). For example, in a seasonal forest in Bolivia, Pérez-Salicrup and Barker (2000) reported that cutting lianas at the beginning of the dry season resulted in unchanging pre-dawn water potential for canopy trees throughout the dry season, whereas pre-dawn water potential for canopy trees with lianas present declined during Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Lianas may help maintain tree diversity in the forest by causing tree falls which could reduce the dominance of tree species [4]. Heavy liana loads on trees can cause mechanical damage of the hosts and also reduce their growth rates [5,6]. Additionally, lianas could impact negatively on natural regeneration of trees in forest ecosystems [7].…”
Section: Introductionmentioning
confidence: 99%